Early Lateral Internal Sphincterotomy Versus Conservative Treatment; Our Experience in Treatment of Chronic Anal Fissure in Qazi Hussain Ahmed Medical Complex Nowshera Pakistan - Fazal Ghani, Kamran Hakeem Khan, Kamran Ahmed, Mudassar Shahzad, Shahid Khan, Waseem Yar Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: A chronic anal fissure is a longitudinal tear in the anorectal area beneath the dentate line contributing to chronic pain and emotional stress during defecation. The present study aimed to assess early surgery versus conservative treatment for managing chronic anal fissures. Methodology: This randomized control trial was carried out on 150 chronic anal fissures patients at the Department of General Surgery, Qazi Hussain Ahmed Medical Complex, Nowshera, Pakistan from March 2020 to September 2021. Patients were divided into two groups; Group-I comprised of patients who were treated conservatively and Group II consisted of patients who underwent surgical intervention. Patients above 15 years of age and fit for surgery were enrolled. A Chi-square test was used for correlating the results using SPSS version 24. Results: Of the total patients, there were 132 (88%) male and 18 (12%) female patients. The overall mean age of Group-I and Group-II was 38.7± 6.5 years and 39.6±3.67 years. The prevalence of posterior and anterior located fissures were 136 (90.7%) and 14 (9.3%) respectively. About 86 patients underwent closed LIS, out of which 77 were male and 9 were female. The patient’s main complaints were anal pain followed by bleeding. The response rate to pain relief treatments was 79% in group-I, I, and I and 97% in group II. Conclusion: Our study found that lateral internal sphincterotomy remains the gold standard for the treatment of chronic anal fissures. To avoid recurrence and obtain the best pain relief, LIS remains the gold standard for the treatment of chronic anal fissures. Keywords: Chronic anal fissure, Conservative treatment, surgical intervention.